Analisa Sistem Informasi Penerimaan Calon Taruna (Catar) dengan Menggunakan Metode McCall (Studi Kasus Politeknik Pelayaran Sumatera Barat) - Eva Rianti; Dwi Febrina Barel (Jurnal Informasi dan Teknologi, 2020)
Candidate Admission is an effort of the campus agency to obtain a Candidate Candidate in accordance with the criteria of each campus. With the information system for recruiting prospective cadets, it is expected to be able to overcome the problems that are often faced in accepting prospective cadets. McCall is one model that explains Software Quality Factor or software quality. This model has three main perspectives, namely product operation, product revision, and product transition. Product operation includes several factors, namely correctness, reliability, usability, integrity, and efficiency. The McCall method has good accuracy and detail so that it can be used to test and guarantee the quality of information system software. Testing is done using the McCall method calculation, the final results obtained from the calculation process, namely from the 30 test data there are 40.17% match the data from the system calculation. The sum of normalized matrices with weights per criterion shows alternative ranking closest to the criteria to the farthest from the criteria included in the Good Enough category.